2007
DOI: 10.1103/physrevlett.99.068104
|View full text |Cite
|
Sign up to set email alerts
|

Minimum-Risk Path Finding by an Adaptive Amoebal Network

Abstract: When two food sources are presented to the slime mold Physarum in the dark, a thick tube for absorbing nutrients is formed that connects the food sources through the shortest route. When the lightavoiding organism is partially illuminated, however, the tube connecting the food sources follows a different route. Defining risk as the experimentally measurable rate of light-avoiding movement, the minimum-risk path is exhibited by the organism, determined by integrating along the path. A model for an adaptive-tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 9 publications
2
129
0
Order By: Relevance
“…The plasmodium is a streaming packet of cytoplasm containing many nuclei. In the plasmodial stage, P. polycephalum exhibits an amoeboid type of movement and is known to respond to a variety of environmental stimuli, including light, physical barriers, food sources, and chemical repellants (Nakagaki et al, 2000(Nakagaki et al, , 2007Adamatzky, 2010;Latty & Beekman, 2010). This response can be easily observed with the naked eye as the plasmodium grows, creating new pseudopodia and thickening tubes in some areas and shrinking back pseudopodia and allowing tubes to die in other areas (tubes that were once alive appear white rather than yellow).…”
Section: Slime Moldsmentioning
confidence: 98%
See 1 more Smart Citation
“…The plasmodium is a streaming packet of cytoplasm containing many nuclei. In the plasmodial stage, P. polycephalum exhibits an amoeboid type of movement and is known to respond to a variety of environmental stimuli, including light, physical barriers, food sources, and chemical repellants (Nakagaki et al, 2000(Nakagaki et al, , 2007Adamatzky, 2010;Latty & Beekman, 2010). This response can be easily observed with the naked eye as the plasmodium grows, creating new pseudopodia and thickening tubes in some areas and shrinking back pseudopodia and allowing tubes to die in other areas (tubes that were once alive appear white rather than yellow).…”
Section: Slime Moldsmentioning
confidence: 98%
“…As more materials are exchanged between two parts of a tube, the tube thickens and is reinforced. As fewer materials are exchanged, the tube thins and eventually dies (Nakagaki et al, 2007). Slime molds have been used in several diverse fields of scientific research.…”
Section: Slime Moldsmentioning
confidence: 99%
“…The behavior of plasmodia is very sensitive and intelligent [4], [5], [6], [7], [8], [15], [17], [18], [19]. This behavior can be represented as a bio-inspired game theory on plasmodia [14], i.e.…”
Section: Introduction N the Physarum Chip Project: Growing Computementioning
confidence: 99%
“…Laboratory experiments and theoretical studies have shown that the slime mould can solve many graph theoretical problems, such as finding the shortest path [26][27][28][29][30][31][32][33], shortest path tree problem [34], network formulation and simulation [25,26,37], influential nodes identification [38], connecting different arrays of food sources in an efficient manner [39][40][41][42], network design [43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%